Β-catenin represses expression of the tumour suppressor 15-prostaglandin dehydrogenase in the normal intestinal epithelium and colorectal tumour cells. Issue 9 (14th November 2011) - Smartt, Helena J M; Greenhough, Alexander; Ordóñez-Morán, Paloma; Talero, Elena; Cherry, Catherine A; Wallam, Catherine A; Parry, Lee; Al Kharusi, Manal; Roberts, Heather R; Mariadason, John M; Clarke, Alan R; Huelsken, Joerg; et al.
Abstract : Background: Cyclooxygenase-2 (COX-2) overexpression in colorectal cancer increases levels of its pro-tumorigenic product prostaglandin E2 (PGE2 ). The recently identified colorectal tumour suppressor 15-prostaglandin dehydrogenase (15-PGDH) catalyses prostaglandin turnover and is downregulated at a very early stage in colorectal tumorigenesis; however, the mechanism responsible remains unclear. As Wnt/β-catenin signalling is also deregulated early in colorectal neoplasia, a study was undertaken to determine whether β-catenin represses 15-PGDH expression. Methods: The effect of modulating Wnt/β-catenin signalling (using β-catenin siRNA, mutant TCF4, Wnt3A or GSK3 inhibition) on 15-PGDH mRNA, protein expression and promoter activity was determined in colorectal cell lines by immunoblotting, qRT-PCR and reporter assays. The effect of β-catenin deletion in vivo was addressed by 15-PGDH immunostaining of β-catenin −/lox -villin-creERT2 mouse tissue. 15-PGDH promoter occupancy was determined using chromatin immunoprecipitation and PGE2 levels by ELISA. Results: The study shows for the first time that β-catenin knockdown upregulates 15-PGDH in colorectal adenoma and carcinoma cells without affecting COX-2 protein levels. A dominant negative mutant form of TCF4 (dnTCF4), unable to bind β-catenin, also upregulated 15-PGDH; conversely, increasing β-catenin activity using Wnt3A or GSK3 inhibition downregulated 15-PGDH. Importantly, inducible β-catenin deletion in vivo also upregulated intestinal epithelial 15-PGDH. 15-PGDH regulation occurred at the protein, mRNA and promoter activity levels and chromatin immunoprecipitation indicated β-catenin/TCF4 binding to the 15-PGDH promoter. β-catenin knockdown decreased PGE2 levels, and this was significantly rescued by 15-PGDH siRNA. Conclusion: These data suggest a novel role for β-catenin in promoting colorectal tumorigenesis through very early 15-PGDH suppression leading to increased PGE2 levels, possibly even before COX-2 upregulation.